2022
DOI: 10.1002/ueg2.12240
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and timely diagnosis of Eosinophilic Esophagitis improves over time in Europe. An analysis of the EoE CONNECT Registry

Abstract: Background Poor adherence to clinical practice guidelines for eosinophilic esophagitis (EoE) has been described and the diagnostic delay of the disease continues to be unacceptable in many settings. Objective To analyze the impact of improved knowledge provided by the successive international clinical practice guidelines on reducing diagnostic delay and improving the diagnostic process for European patients with EoE. Methods Cross‐sectional analysis of the EoE CONNECT registry based on clinical practice. Time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 65 publications
(130 reference statements)
0
18
0
Order By: Relevance
“…Undoubtedly, the present study from Navarro and colleagues 10 provides an optimistic compelling proof on how resources spent on educational initiatives and disease awareness for secondary prevention may result in significant improvements in the disease course and patients' lives. However, this kind of initiatives may still be insufficient for complex disorders like IBD.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Undoubtedly, the present study from Navarro and colleagues 10 provides an optimistic compelling proof on how resources spent on educational initiatives and disease awareness for secondary prevention may result in significant improvements in the disease course and patients' lives. However, this kind of initiatives may still be insufficient for complex disorders like IBD.…”
mentioning
confidence: 69%
“…In this issue of the United European Gastroenterology (UEG) Journal, Navarro and colleagues provide a clear answer through a detailed analysis of the EoE CONNECT database. 10 The aforementioned results observed in EoE resemble some aspects also found in inflammatory bowel disease (IBD). Both are immune-mediated diseases, leading to chronic structural damage of the gastrointestinal tract, with a peak incidence in young adults.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In a cross‐sectional analysis of the international EoE CONNECT registry of EoE, Navarro et al investigated whether the diagnostic process of EoE was effectively improved by release of such guidelines. Interestingly, they found that duration of diagnostic process, percentage of patients with strictures at diagnosis, and severity of disease as assessed by patient‐reported Dysphagia Symptoms Score, were all significantly improved, 10 thus indicating that the European collaborative guidelines on EoE had a major positive impact on the management of these patients.…”
mentioning
confidence: 99%